(untitled) (Development Service Industry Management, 2024)
This article is dedicated to the strategic management of human resource policy and human capital in the agricultural sector, analyzing key aspects and proposing practical approaches to optimizing management practices. It discusses how the selection and placement of qualified personnel impact the efficiency of production processes and the competitiveness of companies in the international market environment. The article offers strategies to enhance employer attractiveness through development and training programs that foster key competencies and adapt to changes in production processes. Special attention is given to the study of human capital management strategies that promote the recruitment of talented employees and their retention and development within the company over the long term. The importance of a motivation and incentive system based on fair working conditions, competitive wages, and career growth opportunities is substantiated. The article also examines the impact of technological innovations on the human resource policies of agricultural enterprises, highlighting how the implementation of modern information systems and the automation of production processes contribute to optimizing management decisions and increasing labor productivity. The necessity of a systematic approach to managing the human potential of the agricultural sector, considering industry specifics and modern market requirements, is emphasized. The strategic management aimed at creating a stable human capital base is described as a critical factor in the success of agricultural enterprises in the global economy.